Lectures on clinical psychiatry - Kraepelin, Emil, 1856-1926 (Harvard medicine preservation microfilm project., 1904)
This book presents various lectures in the field of clinical psychiatry. It is the author's intent to preserve, in a measure, the impressions of a school term's clinical work. In these lectures, the diagnostic point of view is kept in the foreground, the author being convinced of its fundamental importance, not only to our scientific ideas, but also as affecting the advice given in medical practice and methods of treatment adopted by practitioners. The aim of the lectures is to be a guide to the clinical investigation of those with mental disorders. (PsycINFO Database Record (c) 2005 APA, all rights reserved)